Analisis Nilai Tambah Produk Olahan Jagung Manis (Studi Kasus: Usaha F1 Aina Nagari Batu Hampa Kecamatan Akabiluru Kabupaten Lima Puluh Kota ) - Elva Rahmi Fitri; Zednita Azriani; Syahyana Raesi (Journal of Agribusiness and Community Empowerment (JACE), 2021)
The aims of this research were to describe the processing of sweet corn, to analyze the value-added and distribution of value-added becomes peas,corn on the cob,  donuts, grits, and  bakwan  on the business F1 Aina Batu Hampa. This study was conducted  from  March to  April 2016.  The study employed a  case study method.  The study used  Hayami method  in analyzing the value added. The results of this  study showed that the value added generated by Aina F1  was high. It can be seen through the ratio of value added that  is  greater than 40 percent  and varied among products where; 71.76 percents for corn peas, 58.65 percents for corn on the cob, 71.71percents for donuts, 74.40 percents for the grits, and 63,49 percents for bakwan. The product of Sweet corn that generate the highest value added is grits. The ratio of value added can be seen through the margin value distributed in production factors. The highest  of  portion  of value-added received by  the company and the smallest portion  value-added received by the labor.   The largest distribution margin is for the profit of the company. The company's biggest profits come from corn on the cob, followed by grits, peas, donuts, and bakwan. The largest distribution of other input contributions is bakwan, followed by donuts, peas, grits, and  corn of the cob. The distribution of margins received by workers is the smallest part compared to the margins for other input contributions and company profits. The largest distribution is for bakwan , followed by donuts, peas, grits, and corn of the cob.